Use of The Zero Run-Off System to Minimaze of Surface Run Off on Cacao Land. (November 2019) - Suhardi,; Munir, A; Faridah, S N; Waris, A; Sapsal, M T; Samsuar,
Abstract: The decline quality of land of cocoa plantations mainly due to erosion by run off. The application of the Zero Run-off system can reduce rill erosion by eliminating surface runoff. The study was conducted to get the dimensions and layout of the system of Zero Run-Off is effective in improving infiltration so there is no runoff. Dimensions of the system is designed using the water balance approach, where all runoff accommodated in the zero Run- off system then infiltrated. Surface runoff calculated by the method of the Soil Conservation Service (SCS). Potential rate of water inflow into the soil is a function of the saturated hydraulic conductivity of the soil and the surface area of the system. Soil hydraulic conductivity is determined by the falling head method. Dimensions of the system known through a simulation model based on the physical condition data of field using a dynamic model. The simulation results show that the dimensions of the system are required to enter the entire runoff into the ground in the form of infiltration is a function of rainfall, catchment area and the soil saturated hydraulic conductivity. Using this data, the dimensions and position of the systems zero run-off can be determined accurately. For the conditions of research sites, the whole wet surface area of the system at 5 x 106 mm2 per m2. With a broad measure of the volume of water present in the systems of 0 to 0.0000055 m3, so that the system depths of 1, 000 mm, then there is no runoff occurs.